Peasant metropolis : social identities in Moscow, 1929-1941 - Hoffmann, David L. (David Lloyd), 1961- (Studies of the Harriman Institute., 1994)
During the 1930s, 23 million peasants left their villages and moved to Soviet cities, where they accounted for almost half of the urban population and more than half of the nation's industrial workers. Drawing on previously inaccessible archival materials, David L. Hoffmann shows how this massive migration to the cities - an influx unprecedented in world history - had major consequences for the nature of the Soviet system and the character of Russian society even today.